A flexible strain sensor based on MXene/AgNW composite film with extremely high sensitivity and low strain range for real-time health monitoring and thermal management. (11th May 2023) - Qin, Wenfeng; Geng, Junheng; Lin, Chuanxi; Xue, Yunsheng; Zhong, Mian; Zou, Yao; Liu, Guochun; Zhang, Ting
Abstract: Flexible electronic devices have received increasing attention due to their potential applications in wearable human motion and healthcare monitoring and thermal management. Nevertheless, flexible electronic devices for more precise health monitoring of human physiological movement under low strain are still a pressing issue to solve. Herein, a wearable flexible strain sensor with a three-dimensional (3D) conductive network is developed for healthcare monitoring and thermal management by embedding silver nanowires (AgNWs) and Ti3 C2 T x MXene composite films into a polydimethylsiloxane matrix. The sensor can be utilized for human health monitoring, pulse detection at the wrist, and breathing monitoring of human physiological movement due to its low strain detection capacity (0.05% strain) and high sensitivity (gauge factor up to 9472). The primary detection range of the sensor is 0%–1% of tiny strains. Moreover, the exceptional electric heating and optothermal effect supported by the AgNWs and MXene protects human health in extremely cold environments. The MXene/AgNW strain sensor with high sensitivity under low strain has great potential for more precise health monitoring of human physiological movements and thermal management.